Portfolio performance management in new product development : examining the influence of Feedforward anticipatory control on portfolio value and strategic alignment - Baker, Mark (Cranfield University, 2013)
The organization I work in has 13 subsidiary businesses operating in the branded footwear and apparel industry. The industry currently faces significant macroeconomic and industry challenges. One of our biggest challenges is how to avoid excessive and wasteful new product development whilst still building an attractive range of products for the customer. So the focus of my research is on the management control and governance of the New Product Development (NPD) process to solve a pressing business problem. However, there is a gap in the literature. Many authors have claimed that our knowledge of the governance of NPD processes is incomplete and there is a dearth of actual studies in this area. My literature review looked at management control and in particular at the enduring problem of the need to generate control without stifling creativity. The literature led me to focus on the use of feedforward controls to influence NPD management teams to improve portfolio value and strategic alignment whilst simultaneously encouraging NPD experimentation. During this research I developed the concept of Feedforward Anticipatory Control (FAC), which encompasses the combination of feedforward control and double-loop learning. From this start my research question became “How does the use of FAC influence NPD management teams to improve portfolio value and strategic alignment?” From theory and my initial case study research I developed, tested and refined a tool for ascertaining the level of FAC sophistication in use by NPD teams in their development process. The tool was then used in action research interventions to help the teams develop their sophistication in the use of FAC. The tool was found to be useable, useful and have value. The action research case studies were embedded in a case study protocol to ensure the rigour of my research. This involved developing a framework to investigate the consequences of my interventions, in terms of both hard performance metrics and softer team perceptions. The contribution is in the use of management controls in NPD. The findings show that different levels of FAC sophistication can be applied in NPD and that the use of higher levels of FAC influences NPD teams to improve portfolio value and strategic alignment. The contribution to practice is an intervention “toolkit” that can influence NPD teams to develop higher levels of FAC sophistication and generate improvements in NPD portfolio performance.
Keywords: Feedforward control; new product development; portfolio management; performance management